Pengaruh Pembayaran Digital terhadap Usaha Mikro Kecil Menengah (UMKM): Literatur Review - Annisa, Hanif Khoti; Nurbaiti, Annisa; Sundari, Wiwik; Sari, Shella Permata (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research aims to determine the influence of digital payments on Micro, Small and Medium Enterprises (MSMEs). This research uses the Systematic Literature Review method using journal keywords on the influence of digital payment on micro, small and medieum entreprises (MSMEs). This research data comes from journals from 2020 to 2023. The research results show that the influence of digital payments on MSMEs shows that digital payments have several benefits felt by MSMEs. The results of the influence of digital payments on MSMEs show that there are benefits for MSMEs, such as increasing income, improving financial performance, and making transactions easier, thereby supporting business growth. This benefit helps consumers and MSMEs minimize the time and effort required to carry out transactions, as well as providing convenience with flexible payment options. The suggestion for using digital payments for MSME players is to collaborate on payments via a digital system, because using digital payments is considered capable of having a positive influence on their business income. However, MSME players must also be aware of various digital payment risks that may occur.